Evaluation and forewarning of the resource and environmental carrying capacity from the perspective of pressure-support-adjustment: a case study of Yichang city, China - Peng, Ying; Zhu, Zhanglin; Tan, Xingyu; Liu, Xian; Liao, Jiayun; Xiang, Luojing; Wu, Feng (Frontiers in Environmental Science, 2024)
Resources and the environment are essential for socioeconomic development. A scientific and reasonable evaluation and forewarning of the resource and environmental carrying capacity (RECC) is of great significance for regional sustainable development. Although great progress has made in existing research on RECC, there is still no consensus on the definition, evaluation and forewarning method for RECC. Therefore, this study introduced the novel concepts of pressure, support and adjustment, proposed a theoretical framework of RECC reflecting the interaction between the above three, constructed a new evaluation index system of RECC, evaluated RECC based on the ratio method, identified important influencing factors using obstacle model, and put forward the hierarchical forewarning method of RECC with the threshold of 1. Finally, a case demonstration in regard to Yichang city, with a prominent ecological and economic status as the location of China’s Three Gorges Project, was conducted. The results revealed that: 1) The average pressure, support, and adjustment exhibited overall upward trends. The pressure and adjustment increased from west to east, while the support of central districts was relatively lower. 2) The RECC of Yichang city and counties improved from 2016 to 2021, increasing from west to east, and the differences in the RECC of various counties were remarkable but gradually shrank. 3) The RECC of Yichang city remained at the Non-Alert Level. The number of counties with RECC values at Alert Level II decreased from two to zero, and the number of counties at the Non-Alert Level increased from eight to ten. Xiaoting and Zhijiang, with more RECC values at Alert Level II, should receive more attention. This study is expected to enrich the methodology of RECC evaluation and forewarning, and provide possible implications for economic development and environmental protection planning in Yichang and other cities of the same type.